Polio : an American story - Oshinsky, David M., 1944- (Oxford ; New York : Oxford University Press, 2005)
[This book] tells the ... story of the polio terror and of the intense effort to find a cure, from the March of Dimes to the discovery of the Salk and Sabin vaccines--and beyond.-Dust jacket.
The first epidemics -- Warm Springs -- "Cripples' money" -- "And they shall walk" -- Poster children, marching mothers -- The apprenticeship of Jonas Salk -- Pathway to a vaccine -- The starting line -- Seeing beyond the microscope -- "Plague season" -- The rivals -- "The biggest public health experiment ever" -- The Cutter fiasco -- Mission to Moscow -- Sabin Sundays -- Celebrities and survivors.
Includes bibliographical references and index.
Keywords: Poliomyelitis -- United States -- History -- 20th century; a -- Histoire -- 2; 2; Geschichte 1900-2000.; USA; Poliomyelitis; United States; 1900 - 1952; History